1993
DOI: 10.2307/2061647
|View full text |Cite
|
Sign up to set email alerts
|

Religion as a determinant of marital stability

Abstract: Using data from the 1987-1988 National Survey of Families and Households, this paper studies the role of the religious composition of unions as a determinant of marital stability. With the exceptions of Mormons and individuals with no religious identification, stability is found to be remarkably similar across the various types of homogamous unions. Consistent with the notion that religion is a complementary marital trait, interfaith unions have generally higher rates of dissolution than intrafaith unions. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
277
1
6

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 335 publications
(298 citation statements)
references
References 23 publications
14
277
1
6
Order By: Relevance
“…There is less efficiency and more conflict in households where the partners do not share the same affiliation, and consistent with this, religious heterogamy is associated with a higher rate of marital instability, especially if one of the partners is affiliated with a faith near the exclusivist end of the ecumenical-exclusivist continuum (Becker et al 1977;Lehrer and Chiswick 1993; see also Vaaler et al 2009). In addition, consistent with their higher expected rate of divorce, there is some evidence that inter-faith couples restrict their fertility (Becker et al 1977;Lehrer 1996) and have elevated levels of female employment (Lehrer 1995).…”
Section: Religion Human Capital Investments and The Family In The Unmentioning
confidence: 65%
See 2 more Smart Citations
“…There is less efficiency and more conflict in households where the partners do not share the same affiliation, and consistent with this, religious heterogamy is associated with a higher rate of marital instability, especially if one of the partners is affiliated with a faith near the exclusivist end of the ecumenical-exclusivist continuum (Becker et al 1977;Lehrer and Chiswick 1993; see also Vaaler et al 2009). In addition, consistent with their higher expected rate of divorce, there is some evidence that inter-faith couples restrict their fertility (Becker et al 1977;Lehrer 1996) and have elevated levels of female employment (Lehrer 1995).…”
Section: Religion Human Capital Investments and The Family In The Unmentioning
confidence: 65%
“…At the same time, non-Orthodox Jews tend to display opposite patterns, including delayed entry to marriage (Lehrer 2004b), low fertility (Mosher and Hendershot 1984); high educational attainment (Chiswick 1988;Lehrer 1999); high level of female employment except when young children are present in the household (Chiswick 1986;Hartman and Hartman 1996); high wages (Chiswick 1988;Lehrer 2005) and high levels of wealth (Keister 2003(Keister , 2005(Keister , 2009a). Research on Mormons shows a pattern of unusually high fertility (Heaton 1986;Lehrer 1996); high marital stability among homogamous unions (Lehrer and Chiswick 1993); a low level of female employment (Heaton and Cornwall 1998) and low female wages (Lehrer 2005). As to Catholics, the major drop in religious commitment that followed Vatican II (Finke and Stark 2006) led to a convergence to the mainline Protestant pattern in virtually all areas of economic and demographic behavior Lehrer 1995Lehrer , 1999.…”
Section: Religion Human Capital Investments and The Family In The Unmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in marriage studies, researchers found that religious homogamy promoted marital stability, satisfaction, and happiness (Albrecht et al, 1983;Glenn, 1982;Heaton, 1984;Heaton et al, 1985;Lehrer and Chiswick, 1993;Ortega et al, 1988;Heaton and Pratt, 1990). …”
Section: In-group Identity Preferencementioning
confidence: 99%
“…1 Following the seminal work of Azzi and Ehrenberg (1975), economists have explored the potential interactions between religion and a variety of socio-economic variables. For example, Lehrer and Chiswick (1993) investigated religion's effects on marriages, Lehrer (1995), Lehrer (1996), and Lehrer (1999) on labor supply, fertility, and educational attainment, respectively. Barro More recently, research on the relationship between religion and its socio-economic correlates has demonstrated that countries with higher levels of religiosity are characterized by higher levels of income inequality (Palani 2008, Rees 2009).…”
Section: Introductionmentioning
confidence: 99%